Building school resilience in high-risk disaster zones: Slamet volcano eruption mitigation education and simulation - Nugroho, Agung; Irawan, Dedy; Mareza, Lia; Wibowo, Anggun Pria (Community Empowerment, 2025)
Schools located in volcanic disaster-prone areas require high levels of preparedness, yet they are often hindered by a lack of practical training. This community service program aims to enhance the disaster mitigation capacity of the school community at SDN Kecil Munggangsari, Banyumas, situated only 8 km from the summit of Mount Slamet. The implementation utilized a participatory educational approach consisting of two stages: disaster management knowledge transfer and practical self-evacuation simulations for students and teachers. Evaluation results showed a significant surge in disaster literacy and skills. Participants' understanding of mitigation procedures increased from 11% to 100%, while practical simulation experience rose from 6% to 100%. These findings confirm that integrating routine simulations into the educational environment is highly effective in transforming theoretical knowledge into actionable life-saving skills. This program recommends the establishment of a sustainable local mitigation curriculum for schools located in primary volcanic danger zones.